Acoustical comfort in building interior during musical production in town residential area of locality. (December 2017) - Flimel, Marián; Dupláková, Darina
This article highlights the negative consequences of the provisional musical performance in the cities, particularly at the places that are not adjusted for this kind of performances. In the article, there is an appeal made to the need for a comprehensive solution in the form of noise studies and also an algorithm of solution is presented. It is important to achieve the permissible values of noise level in front of house facades for obtaining acoustical comfort in interior of buildings. This article presents the solution of the negative consequences of the provisional musical performance in the cities, particularly at the places that are not adjusted for this kind of performances. The solution for practice is the creation of algorithm for solving music performance in the cities.